PHYSICOCHEMICAL AND RHEOLOGICAL CHARACTERIZATION OF NATIVE AND STARCH-FREE Cissus populnea - MATHIAS, IJI E.; JENNIFER, AUDU-PETER D.; NEP E. IRMYA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
This current study is aimed at determining the effect of starch extraction on the physicochemical and rheological properties of Cissus populnea polymer and its suitability as a Pharmaceutical excipient. Cissus populnea polymer was obtained from the fresh inner bark of the stem of Cissus populnea Guill and Perr. Gum samples extracted were labelled native Cissus populnea polymer (nCPP). The starch content of nCPP was digested and subsequently labelled starch free Cissus populnea polymer (sfCPP). The yield for both extracts of the gum was high, with the sfCPP extract being a bit higher. The swelling index of sfCPP was higher than that of nCPP whereas moisture content and moisture sorption capacity of nCPP were higher. The sfCPP possessed higher fundamental characteristics that would make it a more suitable choice as a Pharmaceutical excipient when compared to nCPP. It is therefore recommended as a suitable Pharmaceutical excipient in the formulation of solid, semi-solid and liquid dosage forms.